Does perianth colour affect the seed germination of two desert shrubs under different storage periods and conditions?. (3rd July 2018) - Bhatt, Arvind; Santo, Andrea
Abstract : Haloxylon salicornicum and Salsola vermiculata (Amaranthaceae) are two perennial shrubs producing fruits with differently coloured perianths (yellow vs pink) on separate individuals. To test the impact of different storage periods (four, eight and twelve months) and temperature conditions (freezing, room temperature and natural field temperatures) on the seed germination of the two seed categories, germination tests were carried out on both species. For both species, collected from wild plants in the Arabian desert (Qatar), seed germination was tested under two photoperiods (light 12/12; dark 24 hours) at 20/30°C for winged (intact) and de‐winged seeds. For each species, all the considered factors (perianth colour, wing presence, photoperiod, storage period and storage conditions) had significant effects on seed germination (p < 0.001), while the interactions among factors varied in their level of significance depending on the species. In both species, yellow seeds germinated considerably better than the pink ones, the presence of wings slowed the germination, and both storage period and temperature conditions highly influenced their germination ability. Our results indicate that seeds from different perianth colours have different germination strategies to delay their germination and distribute the species through time by escaping germination time by imposing some kind of after‐ripening or seed dormancy. The variation in storage time and storage conditions might help in extending their germination period, where one set of seeds germinate immediately, and the other set of seeds becomes dormant and thus contributes to the formation of a soil seed bank for the long‐term recruitment of seedlings. This study highlights an ecological advantageous strategy for these two species growing in the unpredictable desert habitat.